Pleomorphic adenoma with extensive squamous metaplasia: The first well-documented case involving the submandibular gland - Gaskin, David A.; Reid, Alain; Gaskin, Pamela S. (Human Pathology Reports, 2022)
Pleomorphic adenoma with extensive squamous metaplasia is relatively uncommon. Most reported cases in the English literature have involved the minor salivary glands. A 49-year-old male presented with a 5-year history of a right submandibular lump diagnosed as an adenoma on ultrasound. Excision was conducted under general anesthesia. Histological evaluation revealed a pleomorphic adenoma with extensive squamous metaplasia. Pleomorphic adenoma with extensive squamous metaplasia can present a diagnostic dilemma as the differential diagnoses include benign and malignant entities, this is particularly so for small biopsy specimens. We describe an unusual occurrence of this entity in a major salivary gland and discuss its differential diagnoses.